A Critical Review of Waging in Indonesian Law - Agusmidah Agusmidah; Suria Ningsih (Universitas Muhammadiyah Sidoarjo, 2016)
This article is comprehensive look of waging in Indonesian law. Waging in employment still pose a problem. No details of the principle of fair and decent with the policies or the application of the rules of waging, always give rise to new issues and discourse. For the Government, to apply fair and decent wage does not merely make the norm on paper but should be able to guarantee the implementation of the norms in society. This paper uses the literature method with the concept approach. This article discover that the wage disputes can be avoided whereas industrial society interpret the wages in return for the sacrifice that has been given and is able to meet the needs of food, clothing and housing. Then it is not worth it if one party for their maximum benefit utilizing weakness of workers by making the waging system that ignores the principle of fair and decent.